Acceleration of particles by the fields of wave packets - Buts, V.А.; Kuzmin, V.V.; Tolstoluzhsky, A.P. (Вопросы атомной науки и техники, 2019)
The dynamics of particles in the field of a wave packet excited in a plasma is considered. The conditions are found under which such dynamics is regular, and when it becomes chaotic. It was found that the well-known (phenomenological) criterion for the emergence of dynamic chaos − the criterion for overlapping Chirikov nonlinear resonances − requires careful use. Розглянута динаміка частинок у полі хвилевого пакету, що збуджений у плазмі. Знайдено умови, при яких така динаміка є регулярною, і коли вона є хаотичною. Виявлено, що відомий (феноменологічний) критерій виникнення динамічного хаосу − критерій перекриття нелінійних резонансів Чирікова, вимагає обережного використання. Рассмотрена динамика частиц в поле волнового пакета, который возбужден в плазме. Найдены условия, при которых такая динамика является регулярной, и когда она становится хаотичной. Обнаружено, что известный (феноменологический) критерий возникновения динамического хаоса – критерий перекрытия нелинейных резонансов Чирикова, требует осторожного использования.